2020
DOI: 10.1017/s135561772000048x
|View full text |Cite
|
Sign up to set email alerts
|

Montreal Cognitive Assessment (MoCA) Performance and Domain-Specific Index Scores in Amnestic Versus Aphasic Dementia

Abstract: Objective: The Montreal Cognitive Assessment (MoCA) is a popular and simple-to-administer screening instrument to detect cognitive impairment. The MoCA generates a total score and six domain-specific index scores: (1) Memory, (2) Executive Functioning, (3) Attention, (4) Language, (5) Visuospatial, and (6) Orientation. It is unclear whether these MoCA scores can differentiate between distinct clinical dementia syndromes. This study compared MoCA Index scores between amnestic dementia of the Alzheimer’s ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 19 publications
2
15
0
Order By: Relevance
“…This classification means that the patients' clinical pictures did not suggest a specific syndrome, but instead a general language impairment that was evident in functional communication [141] in the form of phonological or semantic paraphasias, which are syntactic or word-finding disorders (Table 1). In line with this, they also showed difficulties in naming, sentence repetition, verbal fluency, and verbal memory in the MoCA test (see Supplementary Table S3) [63,140].…”
Section: Participantssupporting
confidence: 65%
See 1 more Smart Citation
“…This classification means that the patients' clinical pictures did not suggest a specific syndrome, but instead a general language impairment that was evident in functional communication [141] in the form of phonological or semantic paraphasias, which are syntactic or word-finding disorders (Table 1). In line with this, they also showed difficulties in naming, sentence repetition, verbal fluency, and verbal memory in the MoCA test (see Supplementary Table S3) [63,140].…”
Section: Participantssupporting
confidence: 65%
“…For some stroke patients who were part of the large-scale protocol study in Freiburg, it was possible to report the MoCA (Montreal Cognitive Assessment) test scores [63] in the follow-up phase. This test is very sensitive for testing general cognitive abilities, even in patients with anomic deficits [140].…”
Section: Methodsmentioning
confidence: 99%
“…Visuospatial Memory Test-Revised -copy), and language (Boston Naming Test and category fluency -naming animals ) as previously reported 20,25 . Besides MoCA total score, we also calculated MoCA index score for memory, executive function, visuospatia l, language, attention, and orientation 26,27 .…”
Section: Motor Assessment (Gait Fog and Balance Confidence)mentioning
confidence: 99%
“…Some studies were conducted to confirm the differences between clinical groups through the MoCA index score. Wood et al 9 showed that memory and orientation index scores were lowest in the AD group, whereas language and attention index scores were lowest in primary progressive aphasia (PPA). Another study used the MoCA index score for detection of cognitive decline due to neurodegenerative diseases such as AD as well as for confirming the therapeutic effect of alcoholic cognitive decline.…”
Section: Introductionmentioning
confidence: 99%